Crossing the Valley of Death: Managing the When, What, and How of Innovative Development Projects. Issue 4 (August 2019) - Midler, Christophe
The last few decades have seen a profound transformation of innovation project management within automobile firms. During the 1990s, the product development phase was revolutionized by the deployment of heavyweight project management, project portfolio processes, and platform strategies. The 2000s saw the forces of change move upstream in the innovation process, with the development of new methodologies intended to develop and orient creativity, as well as new upfront units acting as innovation labs. However, many upfront creative endeavors still encounter an innovation valley of death when they move into the rigid and risk-averse development phase. Thus, the frontier of innovative project organization seems to be the ongoing quest to reconcile the emergence of breakthrough innovations in the upfront phase with the more rationalized nature of development phases. Based on a case study of a disruptive low-cost car, this article analyzes how the product development phase can support innovative exploration to overcome the challenge of achieving a major cost breakthrough. We analyze the specific content of the project's innovations ( fractal innovation ) and the management practices and organizations used to implement them. We characterize how such innovative product development can contribute to a new economy of innovative effort within the global innovation funnel of the firm. We compare this global innovation process, where development projects play a major role as a locus for organizational learning, to the customary one in automotive firms, where learning happens essentially in front-end marketing and engineering departments.